If an original conditional statement is represented using [tex]\( p \rightarrow q \)[/tex], which represents the converse?

A. [tex]\( \sim p \rightarrow \sim q \)[/tex]
B. [tex]\( -q \rightarrow -p \)[/tex]
C. [tex]\( q \rightarrow p \)[/tex]
D. [tex]\( p \rightarrow q \)[/tex]



Answer :

To solve the problem of identifying the converse of a given conditional statement [tex]\( p \rightarrow q \)[/tex], let's follow these steps:

1. Understand the conditional statement [tex]\( p \rightarrow q \)[/tex]:
- Here, [tex]\( p \)[/tex] is the hypothesis or antecedent.
- [tex]\( q \)[/tex] is the conclusion or consequent.
- The statement reads as "If [tex]\( p \)[/tex], then [tex]\( q \)[/tex]."

2. Define the converse of [tex]\( p \rightarrow q \)[/tex]:
- The converse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is obtained by reversing the hypothesis and conclusion.
- Thus, the converse is [tex]\( q \rightarrow p \)[/tex].
- The converse reads as "If [tex]\( q \)[/tex], then [tex]\( p \)[/tex]."

3. Examine the given options to identify which one represents the converse:

- Option 1: [tex]\( \sim p \rightarrow \sim q \)[/tex]
- This means "If not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]."
- This is actually the inverse of the original statement, not the converse.

- Option 2: [tex]\( - q \rightarrow - p \)[/tex]
- This notation seems to be another way to denote the inverse. However, it's unusual and not standard.

- Option 3: [tex]\( q \rightarrow p \)[/tex]
- This is the direct form of the converse. It means "If [tex]\( q \)[/tex], then [tex]\( p \)[/tex]", which matches our definition of the converse.

- Option 4: [tex]\( p \rightarrow q \)[/tex]
- This is the original conditional statement itself and not the converse.

4. Conclusion:
- Based on our reasoning, the correct option that represents the converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex].
- Thus, the answer is: [tex]\(\boxed{3}\)[/tex].